Aortic distensibility and arterial–ventricular coupling in early chronic kidney disease: a pattern resembling heart failure with preserved ejection fraction. Issue 8 (28th February 2008) - Edwards, N C; Ferro, C J; Townend, J N; Steeds, R P
Abstract : Objectives: To examine arterial and left ventricular function and their interaction in patients with early-stage chronic kidney disease (CKD). Design and setting: Cross-sectional observational study in a university teaching hospital. Patients: 117 patients with stage 2 (60–89 ml/min/1.73 m 2 ) or stage 3 (30–59 ml/min/1.73 m 2 ) non-diabetic CKD, without overt cardiovascular disease were compared with 40 controls. Interventions: Aortic distensibility and left ventricular mass were assessed using cardiac magnetic resonance imaging. Systolic and diastolic ventricular function and arterial–ventricular elastance (stiffness) were assessed by transthoracic echocardiography. Main outcome measures: Arterial stiffness as measured by aortic distensibility and arterial elastance. Left ventricular mass, left ventricular systolic and diastolic function, including end-diastolic and end-systolic elastance and their relationship with arterial elastance. Results: Compared with controls, patients with CKD 2 and CKD 3 had reduced aortic distensibility (4.12 (1.3) vs 2.94 (1.8) vs 2.18 (1.8)×10 –3 mm Hg, p<0.01), increased arterial elastance (1.4 (1.3) vs 1.65 (0.40) vs 1.74 0.48) mm Hg, p<0.05) and increased end-systolic (1.88 (0.48) vs 2.43 (0.83) vs 2.42(0.78) mm Hg/ml, p<0.05) and end diastolic elastances (0.07 (0.04) vs 0.11 (0.04) vs 0.12 (0.04, p<0.01). Aortic distensibility was positively correlated with estimated glomerular filtration rate (r = 0.349, p<0.01) and indices of elastance were inversely correlated (r =  0.284, p<0.05). Systolic function was not impaired in patients with early CKD compared with controls but diastolic filling velocities (Em) were reduced (8.1 (0.9) vs 7.9 (0.6) vs 7.5 (0.7) cm/s, p<0.01) while mean left atrial pressure (E/Em) was increased (5.6 (1.1), vs 7.4 (1.8) vs 8.0 (2.4), p<0.01) and end-diastolic elastance was increased. Conclusions: Early-stage CKD is characterised by reduced aortic distensibility and increases in arterial, ventricular systolic and diastolic stiffness; arterial–ventricular coupling is preserved. This pattern of pathophysiological abnormalities resembles that seen in heart failure with preserved ejection fraction and may account for the high levels of cardiovascular morbidity and mortality in patients at all stages of CKD. Trial Registration Number: NCT00291720